Analisis Kelayakan Penyajian dan Kegrafikaan Dalam Buku Teks Bahasa Indonesia Kelas III Sekolah Dasar - Bening Setia Ilafi; Dedy Irawan (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Textbooks are the most important instructional resources used in schools, and their quality greatly affects the effectiveness of classroom learning. Throughout the learning process, the textbooks used must meet established feasibility standards, particularly in terms of content presentation and graphical elements. This study aims to analyze the feasibility of content presentation and graphical design in the Bahasa Indonesia textbook for third-grade elementary school students published by EG. A qualitative approach with content analysis methodology was employed. The findings show that the textbook's presentation is well-structured and detailed, the layout and composition are visually proportional and harmonious. The cover design utilizes fresh and contrasting colors, the dimensions and format of the textbook are carefully and accurately designed. Images and illustrations are realistic and appropriate, avoiding potential student misinterpretations. This study concludes that the Bahasa Indonesia textbook published by EG a meets the feasibility criteria for both presentation and graphical design and is therefore suitable for use as a companion textbook during the learning process. Buku teks menjadi sumber ajar paling penting dalam kegiatan pembelajaran di sekolah, sehingga kualitas buku teks sangat berpengaruh terhadap efektivitas pembelajaran di sekolah. Selama proses pembelajaran, buku teks yang digunakan harus memenuhi standar kelayakan terutama kelayakan penyajian dan kegrafikaan. Penelitian ini bertujuan untuk menganalisis kelayakan penyajian dan kegrafikaan pada buku teks Bahasa Indonesia kelas III Sekolah Dasar dari penerbit EG. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis konten. Penyajian buku tersusun secara terstruktur dan rinci, tata letak dan komposisi buku terlihat proporsional dan harmonis. Kulit buku menggunakan kontras warna yang segar, ukuran dan bentuk buku teks didesain dengan rinci dan aktual. Gambar dan ilustrasi sesuai dengan kenyataan sehingga tidak menyebabkan salah tafsir siswa. Penelitian ini menunjukan bahwa buku teks EG sudah memenuhi kriteria kelayakan penyajian dan kegrafikaan sehingga layak digunakan menjadi buku teks pendamping selama proses pembelajaran oleh siswa.